On sufficiency and duality in multiobjective programming problem under generalized α-type I univexity - Jayswal, Anurag (Journal of global optimization, 2010)
In this paper, we are concerned with the multiobjective programming problem with inequality constraints. We introduce new classes of generalized α -univex type I vector valued functions. A number of Kuhn–Tucker type sufficient optimality conditions are obtained for a feasible solution to be an efficient solution. The Mond–Weir type duality results are also presented.